2009
DOI: 10.1590/s0104-07072009000100007
|View full text |Cite
|
Sign up to set email alerts
|

A busca por cuidado empreendida por usuário com diabetes mellitus: um convite à reflexão sobre a integralidade em saúde

Abstract: Estudo de caso que objetivou compreender a trajetória empreendida por um usuário com Diabetes mellitus, proveniente do município de Sorriso-MT, ao buscar atendimento às suas necessidades de saúde, bem como analisar a lógica que o direcionou nessa busca, tendo por perspectiva o princípio da integralidade da atenção à saúde. A coleta de dados foi realizada pela entrevista em profundidade e nos permitiu desenhar o Itinerário Terapêutico empreendido pelo usuário na sua busca por cuidados. Dos dados emergiram três … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 3 publications
0
2
0
8
Order By: Relevance
“…These people extend the potential of family care as they allow the development of means to face the many difficulties of the disease process and treatment. 28 As evidenced in a study that addressed the search for care of a person with a chronic disease, diabetes mellitus, 29 it was observed that the young man and his family also gave their own logic to their search, intensely mobilizing people of their own social context for getting responses for their needs more effectively. From these networks that were created, the family received diverse help, as shown in the statements: [.…”
Section: Use Of the Eco-map In The Explanation Of Network For Carementioning
confidence: 99%
“…These people extend the potential of family care as they allow the development of means to face the many difficulties of the disease process and treatment. 28 As evidenced in a study that addressed the search for care of a person with a chronic disease, diabetes mellitus, 29 it was observed that the young man and his family also gave their own logic to their search, intensely mobilizing people of their own social context for getting responses for their needs more effectively. From these networks that were created, the family received diverse help, as shown in the statements: [.…”
Section: Use Of the Eco-map In The Explanation Of Network For Carementioning
confidence: 99%
“…They started to twist me for a while [ The care search trajectories are marked by the arduous pilgrimage of who seeks public health services, partially caused by the low problem-solving ability and integrality of the professional practices offered. 4,17 André's experience reveals a service that, according to him, went "twisting, twisting, twist-ing…", which, in his words, transmits the feeling of delay, of something whose solution takes a long time, or even that never gets solved. In this case, the mediator took a stand in between the patient and the service, so as to gain a solution to the problem from the second.…”
Section: Got There and She Was Ready I Don't Occupy Paper I Don'tmentioning
confidence: 99%
“…Cada familiar de André é afetado pelo início do adoecimento de um modo particular e relembra esse momento relacionando-o à participação que cada um teve na busca por cuidado. A família pode ser considerada como um corpo social, uma rede de interações, assumindo diferentes formas, construindo objetivos e tomando decisões; e, enquanto grupo, apresenta uma estrutura de funcionamento interno edificada por posições e papéis (14) . Em nosso estudo, as participações no "cuidar do outro" que adoece não são decididas de modo racional e estratégico, como se os papéis de cada familiar fossem pensados visando a um objetivo comum a todos, mas se dão como expressão do que cada um pode concretizar no cuidado de quem adoeceu.…”
Section: Impacto Do Diagnóstico De Câncer Sobre Os Familiares Da Pessunclassified
“…As necessidades de cuidado a André provocam uma reorganização familiar para atender a elas. Elas passam a fazer parte da história familiar, gerando tensões e, como consequência destas, modificações na qualidade das interações entre os membros do grupo (14) . Evidenciamos que na família de André essa tensão, em certa medida, ocorre devido aos distintos significados da terapêutica para cada familiar e à necessidade de circular o cuidado entre os laços familiares.…”
Section: Decisões De Busca Por Cuidado E As Diferentes Perspectivas Dunclassified